2014
DOI: 10.1021/jf5025449
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Prevents Fibrillogenesis of Hen Egg White Lysozyme

Abstract: Myricetin is a natural flavonol found in many grapes, berries, fruits, vegetables, and herbs as well as other plants. Recent studies have identified potential antiamyloidogenic activity for this compound. In this study, the kinetics of amyloid fibril formation by hen egg white lysozyme (HEWL) and the antifibril-forming activity of myricetin were investigated. We demonstrate that myricetin significantly inhibits the fibrillation of HEWL and the inhibitory effect is dose-dependent. Interestingly, the inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 65 publications
(89 reference statements)
2
24
0
Order By: Relevance
“…Furthermore, numerous reports have suggested that the antioxidant property of a polyphenol is involved in its anti-amyloidogenic activity [64][65][66]. Given the fact that both RA and Res are potent antioxidants [40,41], a combination of aromatic/hydrophobic interactions and antioxidative properties may contribute to the anti-amyloidogenic activity of the polyphenols [22,36,[67][68][69]. Further work, would be needed to confirm this hypothesis.…”
Section: Ra and Res Inhibit Hewl Fibril Formation And Disaggregates Hmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, numerous reports have suggested that the antioxidant property of a polyphenol is involved in its anti-amyloidogenic activity [64][65][66]. Given the fact that both RA and Res are potent antioxidants [40,41], a combination of aromatic/hydrophobic interactions and antioxidative properties may contribute to the anti-amyloidogenic activity of the polyphenols [22,36,[67][68][69]. Further work, would be needed to confirm this hypothesis.…”
Section: Ra and Res Inhibit Hewl Fibril Formation And Disaggregates Hmentioning
confidence: 98%
“…We have previously demonstrated the effectiveness of indole derivatives to diminish HEWL fibrillation and to disaggregate preformed amyloid fibrils [35]. Several naturally occurring polyphenols, including myricetin [36], (−)-epicatechin gallate [37], curcumin and kaempferol [38], have been reported to markedly inhibit HEWL fibril formation. Studies by He et al have indicated that tea catechins polyphenols convert preformed lysozyme fibrils to amorphous aggregates [39].…”
Section: Q2mentioning
confidence: 99%
“…is already a proven model for examining amyloid fibril formation. 75,76 Among them, 9 amino acids are very important and carry the ability of self-fibrillation called K-peptide. 74 Considering this, we compared the chelerythrine binding region to that of the amyloidogenic aggregation prone region.…”
Section: Comparing Aggregation Prone Region With Chelerythrine Bindinmentioning
confidence: 99%
“…Numerous researchers have investigated the inhibition of LYS amyloid formation. This has resulted in a list of compounds that either partially or completely inhibit fibril formation at acidic pH: food constituents such as short‐chain phospholipids (pH 2.0 and 55 °C) (Wang, Hung, Wen, Lin, & Chen, ), curcumin (Liu et al., ; Wang, Liu, & Lee, ) or its water‐soluble derivatives (Wang et al., ), myricetin (He et al., ), the osmolytes proline, hydroxyproline, sarcosine and trimethylamine N‐oxide (Choudhary & Kishore, ), cysteine (Takai et al., ; Wang, Liu, Wu, & Lai, ), glutathione (Wang, Chou, Liu, & Wu, ), carnosine (Wu et al., ), trehalose, magnesium chloride (Chatterjee, Kolli, & Sarkar, ), safranal, crocin (Joloudar et al., ), zinc ions (Ma, Zhang, Wang, & Zhu, ), aroma components (for example, phenyl ethyl alcohol, N,N,N,N’‐tetramethylethylenediamine, or cinnamaldehyde) (Seraj et al., ), rosmarinic acid, resveratrol (Shariatizi, Meratan, Ghasemi, & Nemat‐Gorgani, ), chemicals such as p‐benzoquinone (Lieu et al., ; Wang, Chen, & Hung, ), 4‐aminophenol and 2‐amino‐4‐chlorophenol (Vieira, Figueroa‐Villar, Meirelles, Ferreira, & De Felice, ), tris(2‐carboxyethyl)phosphine (Wang, Liu, & Lu, ), SDS concentrations of at least 0.25 mM (Hung et al., ), nonionic detergents like triton X‐100 and n‐dodecyl‐β‐D‐maltoside (Siposova, Kozar, & Musatov, ), the ionic liquid tetramethyl guanidinium acetate (Kalhor, Kamizi, Akbari, & Heydari, ), clotrimazole (Sarkar, Kumar, & Dubey, ), sodium tetrathionate (Sarkar, Kumar, & Dubey, ), β‐mercaptoethanol (Sarkar et al., ), glycol‐acridines (Vuong et al., ), 2‐acetyl amin‐3‐[4‐(2‐amintgo‐5‐sulfo‐phenyl]‐propionic acid (Maity et al., ), indole, indole 3‐acetic acid, indole 3‐carbinol, indole 3‐propionic acid and tryptophol (Morshedi, Rezaei‐Ghaleh, Ebrahim‐Habibi, Ahmadian, & Nemat‐Gorgani, ), and other components such as melatonin (Wang, Chen, et al., ), glutathione‐covered gold nanoparticles (Antosova et al., ), manganese–salen derivatives (Bahramikia & Yazdanparast, ; Bahramikia, Yazdanparast, & Gheysarzadeh, ), the crowding agents Ficoll 70 and dextran 70 (Ma et al., ), bovine serum albumin and its combination with Ficoll 70 (Zhou, Zhou, Hu, Chen, & Liang, ), and type I collagen (Dubey & Mar, ).…”
Section: Hen Egg Proteinsmentioning
confidence: 99%
“…Numerous researchers have investigated the inhibition of LYS amyloid formation. This has resulted in a list of compounds that either partially or completely inhibit fibril formation at acidic pH: food constituents such as short-chain phospholipids (pH 2.0 and 55°C) (Wang, Hung, Wen, Lin, & Chen, 2011), curcumin (Liu et al, 2012;Wang, Liu, & Lee, 2009) or its water-soluble derivatives (Wang et al, 2018), myricetin (He et al, 2014) Fibrillation of egg and cereal proteins . .…”
Section: Lysozymementioning
confidence: 99%